2023
DOI: 10.1177/08987564231171529
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Assessment of the Temporomandibular Joint in Asymptomatic Brachycephalic Dogs Using Computed Tomography

Abstract: Temporomandibular joint (TMJ) incongruity and morphological variations can result in clinical signs but have also been reported in asymptomatic brachycephalic dogs. The purpose of this study was to assess TMJ morphology in a group of brachycephalic dogs using computed tomography (CT). French Bulldogs, English Bulldogs, Boxers, Cavalier King Charles Spaniels (CKCS), Chihuahuas, Lhasa Apsos, Pugs, Shih Tzus, and Staffordshire Bull Terriers were retrospectively enrolled. The severity of the TMJ morphological chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…As in two of the previous studies, this study also showed that the Cavalier King Charles Spaniel, the Dachshund, and the French Bulldog had particularly low values for the respective TMJ measurements. These results support the hypothesis of an existing breed predisposition in these dog breeds ( 10–12 ). The French Bulldog was especially different because of its particularly wide and extremely flat joint cavities.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…As in two of the previous studies, this study also showed that the Cavalier King Charles Spaniel, the Dachshund, and the French Bulldog had particularly low values for the respective TMJ measurements. These results support the hypothesis of an existing breed predisposition in these dog breeds ( 10–12 ). The French Bulldog was especially different because of its particularly wide and extremely flat joint cavities.…”
Section: Discussionsupporting
confidence: 89%
“…The canine TMJ has only been studied to a limited extent. This study builds on three previous studies in which morphometric measurements of the canine TMJ were performed ( 5 , 10 , 18 ). In two of the above studies, different breeds of brachycephalic and mesocephalic dogs were analyzed and it was shown that there are breed differences in the congruency of the TMJ, the arrangement of the retroarticular process and the shape of the mandibular fossa.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations